Cyber-Physical Systems: A Literature Review - Sadiku, Matthew N. O.; Wang, Yonghui; Cui, Suxia; Musa, Sarhan M. (European Scientific Journal, ESJ, 2017)
Cyber-physical systems (CPSs) are smart systems that depend on the synergy of cyber and physical components. They link the physical world (e.g. through sensors, actuators, robotics, and embedded systems) with the virtual world of information processing. Applications of CPS have the tremendous potential of improving convenience, comfort, and safety in our daily life. This paper provides a brief introduction to CPSs and their applications.